Pengaruh Competence Terhadap Organization Performance Yang Dimediasi Oleh Strategic Change Management Pada Umkm Di Sidoarjo Saat Pandemi Covid-19 - Ashari, M. Irfan Robby; Sukarno, Gendut; Rini, Hesty Prima (Politeknik Negeri Ambon, 2021)
ABSTRACTThe purpose of this study was to determine whether the variables of strategic change management can be a mediation of the variables of organization performance with variable competence of the organization of Micro, Small and Medium enterprises in Sidoarjo Regency. The primary Data used in this Study was obtained through questionnaires to the target respondents represent the population and secondary data obtained through the official website of the Department of Cooperatives and Micro, Sidoarjo Regency. This study observed the performance of the organization of Micro, Small and Medium enterprises in the District of Sidoarjo. This research uses quantitative analysis to determine the value of the responses of respondents to the variables used in the study, by using the software SmartPLS. The results of this study successfully proved that the strategic change management has the role of mediation between the Competence to Organization performance with the value of the path coefficients of 0,245, and the value of T-statistic of 2,980 > 1,96 (from table value Za = 0,05) or P-values of 0.003 (smaller than 0.05) on the organization of Micro, Small and Medium enterprises in the District of Sidoarjo.Â ABSTRAKPenelitian ini bertujuan untuk mengetahui apakah variabel strategic change management dapat memediasi variabel organization performance dengan variabel competence pada organisasi UMKM yang ada di Kabupaten Sidoarjo. Data primer yang dipakai dalam penelitian ini adalah data yang didapat dari penyebaran kuesioner kepada target responden yang mewakilkan populasi dan data sekunder yang dipakai dalam penelitian ini adalah data yang didapat dari website resmi Dinas Koperasi dan Usaha Mikro Kabupaten Sidoarjo. Penelitian ini menggunakan analisis kuantitatif untuk menentukan nilai respon dari responden pada variabel yang digunakan dalam penelitian, dengan menggunakan piranti lunak SmartPLS. Hasil dari penelitian ini berhasil membuktikan bahwa strategic change management dapat memediasi antara variabel competence dengan variabel organization performance dengan nilai path coefficients sebesar 0,245, dan nilai T-statistic sebesar 2,980 > 1,96 (dari nilai tabel ZÎ± = 0,05) atau P-values sebesar 0,003Â (lebih kecil dari 0,05)